Gene expression profiling of peripheral blood mononuclear cells during treatment with a gene‐modified allogeneic tumor cell vaccine in advanced renal cell cancer: Tumor‐induced immunosuppression and a possible role for NF‐κB. Issue 8 (30th September 2014) - Flörcken, Anne; Grau, Michael; Wolf, Annette; Weilemann, André; Kopp, Joachim; Dörken, Bernd; Blankenstein, Thomas; Pezzutto, Antonio; Lenz, Peter; Lenz, Georg; Westermann, Jörg
<x xml:space="preserve">Abstract</x> Tumor‐induced immunosuppression remains a major challenge for immunotherapy of cancer patients. To further elucidate why an allogeneic gene‐modified [interleukin‐7 (IL‐7)/CD80‐cotransfected] renal cell cancer (RCC) vaccine failed to induce clinically relevant TH‐1‐polarized immune responses, peripheral blood mononuclear cells from enrolled study patients were analyzed by gene expression profiling (GEP) both prior and after vaccination. At baseline before vaccination, a profound downregulation of gene signatures associated with antigen presentation, immune response/T cells, cytokines/chemokines and signaling/transcription factors was observed in RCC patients as compared to healthy controls. Vaccination led to a partial reversion of preexisting immunosuppression, however, GEP indicated that an appropriate TH‐1 polarization could not be achieved. Most interestingly, our results suggest that the nuclear factor‐kappa B signaling pathway might be involved in the impairment of immunological responsiveness and the observed TH‐2 deviation. In summary, our data suggest that GEP might be a powerful tool for the prediction of immunosuppression and the monitoring of immune responses within immunotherapy trials.